Neurofeedback in ADHD - Tomas Ros (Frontiers Research Topics, 2016)
EEG-based neurofeedback is used as a treatment approach in attention-deficit / hyperactivity disorder (ADHD), a clinically and pathophysiologically heterogeneous child psychiatric disorder. There is increasing evidence for specific effects of neurofeedback when applying 'standard' protocols (slow cortical potentials, theta/beta, sensorimotor rhythm). Knowledge about underlying mechanisms and moderating variables is increasing. Nevertheless, further well-controlled and conducted trials are needed to answer open questions concerning optimisation and individualisation of neurofeedback. Further improvements may develop with new methods and technical developments (e.g., tomographic neurofeedback) and new concepts (integrated ADHD treatment). This Frontiers Research Topic comprising 14 articles intends to answer the following questions concerning neurofeedback in ADHD: • How efficacious is neurofeedback? • What is the rationale of applying a certain neurofeedback protocol in ADHD? • What are central mechanisms and which moderating variables may affect training and treatment outcome? • How to optimise treatment? What are new developments and which benefits may be expected? Aspects of learning theory are also stressed dissociating 'neurofeedback as a treatment' and 'neurofeedback as entertainment'. In the Editorial, this crucial aspect is compared to the way you read (and study) a scientific book versus reading a thriller for leisure. In this respect: Enjoy this Research Topic, study and apply it in practice, unless you read it for entertainment purposes!